OPTIMALISASI PERAN SATUAN LALU LINTAS DALAM MENCEGAH KECELAKAAN LALU LINTAS DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi di Satuan Lalu Lintas Wilayah Jakarta Timur, DKI Jakarta) - , Ramsan Sinaga ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research titled \"Optimizing the traffic unit role in preventing traffic accidents and their implications for resistance area (the study of the Police east region Jakarta)\" aims to determine the role of the Regional Traffic Unit in East Jakarta prevent traffic accidents, obstacles the challenges that emerged traffic Unit in preventing traffic accidents, and the implications of the role of Regional traffic Unit in East Jakarta to prevent traffic accidents in retention area. This study uses qualitative analysis. Qualitative analysis is used to describe the role played by the Regional Traffic Unit East Jakarta in preventing traffic accidents and describe the role of implementation constraints and describe the implications of the role of the resistance region. Results of research conducted showed that : The Role of Force in East Jakarta Traffic Police in preventing traffic accidents conducted by performing several steps : first, assesment. The assesment carried out on accident blackspots and went straight to certain spots in the area of East Jakarta. Second, Registration/Driver and Vehicle Identification (Driver and Vehicle Identification). Third, Traffic Law Enforcement (Law Enforcement Police traffic ). Enforcement by the Traffic Police include preventive and repressive. Fourth, Operational management and traffic engineering (Police Traffic Engineering). Fifth, public education about traffic (Traffic Police Education). Education conducted on both two-wheeler riders and four wheels. Driver's education was intensified by the Regional Traffic Unit Jaktim in certain spots. Constraints implementation role in East Jakarta Metro Police traffic cop is the availability of human resources , facilities and infrastructure and the lack of community support. Implications Optimizing the role of Regional Traffic Unit East Jakarta in preventing traffic accidents in retention areas can be summarized as follows : optimization needs to be done by the East Jakarta Metro Police Traffic Unit is to intensify law enforcement/raids in anticipation of the riders who are not orderly. In addition, it is also necessary to revitalize the road traffic signs, strengthening cooperation with various stakeholders associated with the activities and road traffic. Traffic accidents directly affect the security area. In the study it was found that the implications for the resilience of the region on the politic,economic and social aspects of the victims and their families as well as the political and security areas in East Jakarta .